2010
DOI: 10.1016/s2005-2901(10)60049-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Efficacy of Nasturtium officinale Extracts Using Various In Vitro Assay Systems

Abstract: Nasturtium officinale R. Br. (watercress), of the family Brassicaceae, has been long used as a home remedy or a medicinal plant by the people of southeastern Iran. The aim of this study was to investigate the antioxidant activity of N. officinale extract using various in vitro assay systems, including the ferric reducing antioxidant power and 2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonate) assays, 1,1-diphenyl-2-picrylhydrazyl, hydrogen peroxide, nitric oxide radical scavenging, and ferrous ion chelating ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…Generation of ROS has an important role in the development of both TPA and carrageenan-induced inflammation (Fischer et al, 1988;Vircheva et al, 2011). Furthermore, some researchers have established antioxidant effects of N. officinale (Bahramikia & Yazdanparast, 2010;Yazdanparast et al, 2008), hence another possibility is that antioxidant effects of the plant, at least, play a partial role in its antiinflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of ROS has an important role in the development of both TPA and carrageenan-induced inflammation (Fischer et al, 1988;Vircheva et al, 2011). Furthermore, some researchers have established antioxidant effects of N. officinale (Bahramikia & Yazdanparast, 2010;Yazdanparast et al, 2008), hence another possibility is that antioxidant effects of the plant, at least, play a partial role in its antiinflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yazdanparast et al (2008) has reported that watercress supplementation in the diet reduces serum lipids and alters blood antioxidant status in hypercholesterolaemic rats . They also have shown that N. officinale has potent antioxidant properties with in vitro conditions (Bahramikia & Yazdanparast, 2010). To our knowledge, there is no study about the possible anti-inflammatory effects of N. officinale with either in vivo and in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Yazdanparast and colleagues reported that watercress supplementation in diet decreases serum lipids and alters blood antioxidant status in hypercholesterolaemic rats (18). They also reported that it has a potent antioxidant property in vitro and in vitro (18,19). Our previous study showed that watercress produced a noticeable anti-inflammatory effect in different animals of inflammation (17).…”
Section: Introductionmentioning
confidence: 92%
“…The extract also inhibited lipid peroxidation in rat liver homogenate, likely attributable to its ability to chelate Fe 2? ions (Bahramikia and Yazdanparast 2010). In vivo antioxidant effect of hydroethanolic extract of N. officinale was demonstrated by the its ability to increase SOD and CAT activities, reduce lipid peroxidation, and increase GSH levels in the liver Phytochem Rev of hypercholesterolemic rats (Yazdanparast et al 2008).…”
Section: Nasturtium Officinalementioning
confidence: 99%
“…More advanced technologies employed to identify and characterize antioxidants from EFM included HPLC-electrospray ionizationmass spectrometry (HPLC-ESI-MS)(Fu et al 2011), photodiode array detection-electrospray ionizationmass spectrometry (HPLC-DAD-ESI-MS/MS)(Chen et al 2012b), and NMR analysis(Marzouk et al 2007).Multiple in vitro assays have been used to characterize the antioxidant potential of EFM extracts and compounds isolated from them. Such in vitro antioxidant assays included 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay(Anand et al 2010;Ooh et al 2014;Orhan 2012), nitric oxide (NO) scavenging assay(Ooh et al 2014;Rai et al 2006), metal chelating assay(Bahramikia and Yazdanparast 2010;Ooh et al 2014;Orhan 2012), Ferric Reducing Antioxidant Power (FRAP) assay(Anand et al 2010;Orhan 2012), and hydroxyl radical scavenging assay(Anand et al 2010; Das- gupta and De 2007).…”
mentioning
confidence: 99%